2020
DOI: 10.20944/preprints202002.0299.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

scRNA-seq Profiling of Human Testes Reveals the Presence of ACE2 Receptor, a Target for SARS-CoV-2 Infection, in Spermatogonia, Leydig and Sertoli Cells

Abstract: In December 2019, a novel coronavirus (SARS-CoV-2) was identified in patients with pneumonia (called COVID-19) in Wuhan, Hubei Province, China. SARS-CoV-2 shares high sequence similarity and uses the same cell entry receptor, angiotensin-converting enzyme 2 (ACE2), as does severe acute respiratory syndrome coronavirus (SARS-CoV). Several studies have provided bioinformatic evidence of potential routes for SARS-CoV-2 infection in respiratory, cardiovascular, digestive and urinary systems. However, whether the r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
314
0
18

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(336 citation statements)
references
References 15 publications
4
314
0
18
Order By: Relevance
“…Based on scRNA-seq analysis, Wang ZP et al found that TMPRSS2 mainly exists in spermatogonia and spermatids, whereas ACE2 widely expresses in spermatogonia, Leydig and Sertoli cells. Gene ontology (GO) enrichment analysis further indicated that GO categories associated with viral reproduction and transmission were positively enriched in ACE2-positive spermatogonia [9] . SARS, the similar virus of SARS-CoV-2, has been reported to cause orchitis [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Based on scRNA-seq analysis, Wang ZP et al found that TMPRSS2 mainly exists in spermatogonia and spermatids, whereas ACE2 widely expresses in spermatogonia, Leydig and Sertoli cells. Gene ontology (GO) enrichment analysis further indicated that GO categories associated with viral reproduction and transmission were positively enriched in ACE2-positive spermatogonia [9] . SARS, the similar virus of SARS-CoV-2, has been reported to cause orchitis [13] .…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 is enriched in the epithelia of lung [7], while single-cell RNA-seq data analysis of ACE2 expression reveals potential risks of more human organs vulnerable to SARS-CoV-2 infection [8]. In reproductive system, single-cell transcriptomes of adult human testis showed high expression of ACE2 in spermatogonia, Leydig and Sertoli cells [9]. Coronaviruses are prone to mutation and recombination due to their error-prone RNA-dependent RNA polymerase (RdRP) [10], and virus variation may allow some subtypes of the virus to better bind to the receptor ACE2.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, cells that show high level of ACE2 expression have the potential to be targeted and damaged by the virus [2]. Multiple studies detected high ACE2 expression level in testicular cells, mainly in seminiferous duct cells, spermatogonia, Leydig cell and Sertoli cells [2][3][4]. Based on the results of these studies, it is concluded that the testis could be a potential target for direct damage by SARS-COV2 virus.…”
Section: Dear Editormentioning
confidence: 93%